Fullerene Binding Effects in Al(Iii)/Zn(Ii) Porphyrin/Phthalocyanine Photophysical Properties and Charge Transport - Cardenas-Jiron, G; Borges-Martinez, M; Montenegro-Pohlhammer, N (Elsevier B.V., 2022)
We evaluate the fullerene C60 binding effect; through the metal (Al) and through the ligand (Pc,TPP), on the photophysical and charge transport properties of M−porphyrin(TPP)/phthalocyanine(Pc) (M = Al(III), Zn(II)). We perform density functional theory (DFT) and time-dependent DFT calculations for the macrocycle-C60 dyads, showing that all systems studied are thermodynamically favorable. The C60 binding effect on the absorption spectrum is a red-shift of the Q and Soret (B) bands of TPPs and Pcs. The Pc-dyads show longer λ for Q bands (673 nm) than those with TPP (568 nm). AlTPP-C60 and ZnTPP-C60 show a more favorable electron injection to TiO2 than the analogs Pcs, and the regeneration of the dye is preferred in AlTPP-C60 and AlPc-C60. Zero-bias conductance is computed (10-4–10-7 G0) for the dyads using molecular junctions with Au(1 1 1)-based electrodes. When a bias voltage of around 0.6 V up to 1 V is applied, an increase in current is obtained for AlTPP-C60 (10-7 A), ZnTPP-C60 (10-7 A), and AlPc-C60 (10-8 A). Although there is not a unique trend in the behavior of the dyads, Pcs have better photophysical properties than TPPs and the latter are better in the charge transport. We conclude that AlTPP(ZnTPP)-C60 dyads are an excellent alternative for designing new materials for dye-sensitized solar cells or optoelectronic devices. © 2021 Elsevier B.V.